1999
DOI: 10.1128/aac.43.7.1591
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactamase Production by Oral Anaerobic Gram-Negative Species in Infants in Relation to Previous Antimicrobial Therapy

Abstract: The frequency of β-lactamase production in gram-negative bacteria has increased considerably during recent years. In this study, β-lactamase production by oral anaerobic gram-negative rods isolated from saliva was longitudinally examined for 44 Caucasian infants at the ages of 2, 6, and 12 months in relation to their documented exposure to antibiotics. Isolates showing decreased susceptibility to penicillin G (1 μg/ml) were examined for β-lactamase production by using a chromogenic cephalosporin disk test. β-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…and F. nucleatum [1,7]), and 21 aerobic isolates (Haemophilus parainfluenzae, Moraxella catarrhalis and staphylococci [12]) and the relationship between S␤A and data on infants' exposure to antimicrobial agents during the first year of life [7] was examined. Chi-square tests were used to analyse the associations between the presence of ␤-lactamase-producing bacteria and S␤A, and between antimicrobial exposure and S␤A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and F. nucleatum [1,7]), and 21 aerobic isolates (Haemophilus parainfluenzae, Moraxella catarrhalis and staphylococci [12]) and the relationship between S␤A and data on infants' exposure to antimicrobial agents during the first year of life [7] was examined. Chi-square tests were used to analyse the associations between the presence of ␤-lactamase-producing bacteria and S␤A, and between antimicrobial exposure and S␤A.…”
Section: Discussionmentioning
confidence: 99%
“…According to our working hypothesis, harbouring oral ␤-lactamase-producing species is reflected in ␤-lactamase activity in saliva. Since infants' exposure to antimicrobial agents increases the prevalence of ␤-lactamaseproducing species [7], exposure to antimicrobial agents will most likely increase the salivary ␤-lactamase activity as well. In the present study, our aims were, firstly, to examine the frequency of salivary ␤-lactamase activity (S␤A), secondly, to compare this activity with the presence of ␤-lactamaseproducing (␤+) bacteria in saliva, and finally, to estimate the impact of exposure of antimicrobial agents, on the emergence of S␤A in a group of healthy infants during the first year of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] In addition, b-lactamase-producing Bacillus and Pseudomonas species were isolated from subgingival plaque in patients with chronic periodontitis. 36 The Prevotella species has been reported to be the most frequent b-lactamase-producing species found in periodontal pockets and saliva, [36][37][38] and it is frequently detected in infants and healthy young children. 38,39 Isolates of Fusobacterium nucleatum were shown to produce significant amounts of b-lactamase in patients suffering from tonsillitis.…”
Section: B-lactamasesmentioning
confidence: 99%
“…36 The Prevotella species has been reported to be the most frequent b-lactamase-producing species found in periodontal pockets and saliva, [36][37][38] and it is frequently detected in infants and healthy young children. 38,39 Isolates of Fusobacterium nucleatum were shown to produce significant amounts of b-lactamase in patients suffering from tonsillitis. 40 In addition, Kö nö nen et al demonstrated that penicillin resistance caused by b-lactamase production by oral strains of F. nucleatum frequently occurs in childhood.…”
Section: B-lactamasesmentioning
confidence: 99%